Le fonti patristiche e filosofiche del De Trinitate di S. Agostino - Cipriani, Nello (Augustinianum, 2015)
Following some methodological remarks, the article first demonstrates the possibility of determining indirectly Augustine’s patristic sources in De Trinitate, while it also takes into account the author’s indications of his sources in other of his writings. The presence of Marius Victorinus in Books 5-7 is also underscored. The second half of the article, while acknowledging a certain Neoplatonic philosophical influence behind similitudo mentis, nevertheless attributes Augustine’s first awareness of this concept to Victorinus. In addition, the psychological analyses found in Books 9-10 are traceable principally to the theory of oikeiosis present in Latin authors, in primis, Cicero.